A Review Paper on Solar Energy Generation along National Highways (International Journal of Innovative Research in Computer Science & Technology, 2022)
Solar energy as a source of electric power  is gaining traction in Brazil, and it is the topic of global  environmental debates. Electric energy, which is a right of  all people, represents a large-scale use of natural resources.  In 2016, state schools in Paraná spent more over R$ 46  million to provide power and therefore provide the system  with necessary operating conditions. 15 schools in  Curitiba/"Regional PR's Administrative do Cajuru" were  assessed in terms of electric energy usage and expenditures  from January to May 2017, and a solar photovoltaic system  was dimensioned to meet each school's need. It was  calculated that the entire savings from the energy that  would no longer be spent on power could be allocated to  other educational programs and community-oriented  initiatives to help the school achieve sustainability. The  projected yearly savings were more than R$ 435 thousand.
Keywords: Electric; Energy; Resources; Software; Solar